2019
DOI: 10.1002/ajmg.a.61038
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of anxiety symptoms in boys with 47,XXY (Klinefelter syndrome) and the possible impact of timing of diagnosis and hormonal replacement therapy

Abstract: Funding informationThe Focus Foundation 47,XXY (Klinefelter syndrome) is the most common X and Y chromosomal variation (1:660 males). The incidence of anxiety disorders and the impact of hormonal replacement therapy (HRT) is not well understood. Child Behavior Checklist and Screen for Childhood Anxiety Related Emotional Disorders were completed by parents of 80 boys with 47,XXY. Forty received HRT prior to 10 years of age while 40 did not. HRT (22.5%) received early hormonal treatment prior to 18 months. About… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 32 publications
0
26
1
Order By: Relevance
“…Children with these disorders present with dysfunction in speech, language, and motor development . The phenotype spans a wide range of associated symptoms that vary in severity depending on the specific SCA, timing of diagnosis, and family history …”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Children with these disorders present with dysfunction in speech, language, and motor development . The phenotype spans a wide range of associated symptoms that vary in severity depending on the specific SCA, timing of diagnosis, and family history …”
Section: Introductionmentioning
confidence: 99%
“…Over 50 years of publications have demonstrated significant evidence to the importance of early identification of SCAs and the positive impact of early intervention on neurodevelopmental outcomes . These studies have also shown that children prenatally diagnosed with an SCA have less neurodevelopmental dysfunction, fewer behavioral disturbances, and IQs within or above the normal limits.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations